A customized scrum framework for agile implementation of customer relationship management systems: a qualitative study with a Malaysian salesforce implementation partner - Goh, Julian Tok Min (2024)
Despite extensive research on CRM, a critical gap exists – the influence of real-world CRM implementation frameworks on project success. This study addresses this gap alongside the lack of an integrated, agile framework for CRM implementations within Information Systems research. This qualitative case study, which was conducted with a Malaysian Salesforce implementation partner, addresses this gap. It employs a multi-phased approach and includes a pilot study, an in-depth interview with an experienced professional, followed by thematic analysis. This analysis reveals eleven key insights crucial for CRM implementation. Leveraging these insights, this study then proposes a customized Scrum framework specifically designed for agile CRM projects. The framework seamlessly integrates core Scrum principles with the unique needs of CRM implementations. Expert validation further refines the framework and offers a potentially valuable tool for organizations seeking to leverage Scrum for agile CRM projects. This research contributes to the field by: • Unveiling the critical role of CRM implementation frameworks in project success. • Developing a customized Scrum framework for agile CRM implementations. • Expanding the understanding of critical success factors in CRM projects.